Keeping Tradition, Culture, and Community through Social Entrepreneurship: A Case of Lamerenan - Harnadi, Agnes; Sijabat, Rosdiana; Widyastuti, Pristiana; Singgalen, Yerik Afrianto (Bina Nusantara University, 2023)
The research discussed social entrepreneurship that aimed to create social impacts. These impacts could be not only economic, yet cultural. Lamerenan was a social enterprise focused on Tanimbarâ€™s tenun cloth (handwoven fabric) through community empowerment. This foundation was chosen because it encouraged the local community to preserve tradition and culture by persuading them to use traditional methods to produce the cloth. Although this foundation was categorized as a micro-small-medium enterprise (MSME) with age less than ten years old, Lamerenan had a mission to restore the quality of Tanimbarâ€™s tenun cloth, by keeping the tradition using traditional weaving loom, which was called â€œTenun Gedog Loomâ€ or â€œGedoganâ€ and natural dyes. The research utilized the qualitative method. An in-depth interview was conducted with the founder of Lamerenan, Hiyashinta Klise, on December 2021 via Zoom meeting. Secondary data about Lamerenan and Tanimbarâ€™s tenun cloth was collected from online news and Lamerenanâ€™s social media (Instagram). The research finds how Lamerenan keeps the Tanimbarâ€™s weaving tradition, culture, and women weaver community through social entrepreneurship. Furthermore, how the community returns to the traditional way, using natural dyes in producing the cloth. The result of the research is expected to bring insight into local traditions and culture that can be useful in developing empowerment in the local community.